Front Cover: A Combined Experimental–Theoretical Study on Diels‐Alder Reaction with Bio‐Based Furfural: Towards Renewable Aromatics (ChemSusChem 1/2021). Issue 1 (10th December 2020) - van Scodeller, I; De Oliveira Vigier, Karine; Muller, Eric; Ma, Changru; Guégan, Frédéric; Wischert, Raphael; Jérôme, François
Abstract : The Front Cover shows how combining theoretical and experimental investigations allows predicting the feasibility and the selectivity of Diels–Alder reactions involving furfural as a bio‐based diene, opening a straightforward route to renewable aromatics. More information can be found in the Full Paper by I. van Scodeller et al .